2013
DOI: 10.1002/cb.1450
|View full text |Cite
|
Sign up to set email alerts
|

How gender affects the relationship between hedonic shopping motivation and purchase intentions?

Abstract: Five hundred and fifteen consumer responses are used to model the affect of online hedonic shopping motivation and online purchase intentions: moderated by the consumers' perceptions of their offline and online gendered behaviour. The model was applied across five product categories using confirmatory factor analysis and structural equation modelling. We conclude that there is no online‐gender effect on hedonic shopping motivation and purchase intentions. However, offline‐gendered behaviour does significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
53
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 79 publications
(113 reference statements)
7
53
0
1
Order By: Relevance
“…They want quality, convenience, discounts and accessibility while purchasing a product. In context of utilitarian motivation, current study similar to the findings of the previous studies (Yang and Wu, 2006;Swaminathan et al, 1999;Alreck and Settle, 2002) which suggested that males have higher utilitarian motive for shopping compare to females and contradict some previous studies (Davis et al, 2014) which stated that females have higher utilitarian motive than males. In this study, hedonic motivation during shopping found to be prevalent among females than males, which is similar to the Arnold and Reynolds, (2003) statement that is "females are more hedonic-oriented than males when they go to retail stores for shopping" and it also has similarity with the findings of other studies like (Yang and Wu, 2006;Dittmar et al, 2004;Swaminathan et al, 1999;Alreck and Settle, 2002).…”
Section: Resultssupporting
confidence: 64%
See 3 more Smart Citations
“…They want quality, convenience, discounts and accessibility while purchasing a product. In context of utilitarian motivation, current study similar to the findings of the previous studies (Yang and Wu, 2006;Swaminathan et al, 1999;Alreck and Settle, 2002) which suggested that males have higher utilitarian motive for shopping compare to females and contradict some previous studies (Davis et al, 2014) which stated that females have higher utilitarian motive than males. In this study, hedonic motivation during shopping found to be prevalent among females than males, which is similar to the Arnold and Reynolds, (2003) statement that is "females are more hedonic-oriented than males when they go to retail stores for shopping" and it also has similarity with the findings of other studies like (Yang and Wu, 2006;Dittmar et al, 2004;Swaminathan et al, 1999;Alreck and Settle, 2002).…”
Section: Resultssupporting
confidence: 64%
“…Males were found to be more utilitarian-oriented compared to females while shopping (Dittmar et al, 2004). Various studies suggested that shopping behaviour of male and female differs in an online context (Fan and Miao, 2012;Davis et al, 2014). Kim and Forsythe (2008) revealed that male and female having no difference in utilitarian and hedonic motive.…”
Section: Related Review Of Literaturementioning
confidence: 98%
See 2 more Smart Citations
“…Prior studies have shown the importance of gender effect (Davis, Lang, & San Diego, 2014) in retail shopping behavior. Therefore, the sampling for this research is mainly female consumers.…”
Section: Sample and Data Collectionmentioning
confidence: 99%